A Modular Step-Up DC/DC Converter for Electric Vehicles - Ahmed Darwish (Energies)
A step-up DC/DC converter is required to match the fuel cell’s stack voltage with the DC-link capacitor of the propulsion system in fuel cell-based electric vehicles (FCEVs). Typically, the nominal voltage of a single fuel cell ranges from 0.5 V to 1 V, and the DC-link voltage usually lies between 400 V and 800 V. This article proposes a new modular step-up DC/DC converter capable of providing a wide voltage-boosting range from the input to the output side using series-connected isolated boosting submodules (SMs). Modified versions of boost and Cuk converters are designed and used as the SMs to deliver a flexible output voltage, combining the voltage-boosting capability with the ability to embed a medium/high-frequency transformer, which provides both galvanic isolation and an additional degree of voltage boosting while drawing a continuous input current from the fuel cell with minimal ripple, enhancing performance. The proposed modular converter offers the advantages of improved controllability, scalability, and greater reliability, particularly during partial faults. The feasibility of the proposed converter is demonstrated through computer simulations conducted using MATLAB/SIMULINK® R2024a software where a DC link of 400 V is created from 50 V input sources. Additionally, a 1 kW small-scale prototype is designed and controlled using a TMS320F28335 digital signal processor to validate the mathematical analysis and simulation results, where the SMs are controlled to create a DC link of 100 V from four 25 V input sources with an electrical efficiency of approximately 95%.